A Theory of Trading in Stock Index Futures. (5th May 2015) - Subrahmanyam, Avanidhar
Abstract : It is demonstrated that markets in stock index futures or, more generally, in baskets of securities, provide a preferred trading medium for uninformed liquidity traders who wish to trade portfolios, because adverse selection costs are typically lower in these markets than in markets for individual securities. Thus, an explanation is provided for the immense liquidity and popularity of markets in stock index futures. Implications are also developed for the effect of the introduction of a basket on market liquidity and the informativeness and variability of component security prices, and for the price relationship between the basket and its underlying portfolio.